JANGER SEBAGAI SARANA INFORMASI DAN PEMBENTUKAN KARAKTER BAGI MASYARAKAT BANYUWANGI - Lambang Erwanto Suyadjid (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2011)
Abstract. This article reports a study of Janger as one kind of Indonesian traditional arts that has an important role especially in a certain community or region. Janger functions to fulfil the need of Banyuwangi people of entertainment and education or information. Janger has the elements of amusement, validating culture, education, and conformity of patterns of attitude functions in which those are the means of information for the people. The story implied in janger can educate people about life and the other informations of social concern and also as means of character building. Keywords: Janger, amusement, validating culture, education, and conformity of patterns of attitude, character building